Accelerated carbonation of regenerated cementitious materials from waste concrete for CO2 sequestration. (1st September 2022) - Zhang, Yunhua; Chen, Hanping; Wang, Qing
Abstract: Regenerated cementitious materials (RCM) was peeled sufficiently from the surface of aggregate after waste concrete subjected to air cooling after heating at 400 °C and 650 °C and then RCM was utilized to prepare carbonated products by accelerated carbonation for CO2 sequestration. In this study, the effect of the compaction rate of compacted RCM and water-solids ratio (w/s) on the CO2 uptake and mechanical properties of carbonated RCM (C-RCM) was evaluated and the carbon footprint of RCM was assessed. Results indicate the CO2 uptake and compressive strength of C-RCM subjected to 650 °C (C-RCM 650) are higher than that of C-RCM subjected to 400 °C (C-RCM 400) for the higher carbonation activity, larger porosity of compact and lower voids between RCM particles. In consideration of the carbon emissions from the calcination process, the net CO2 uptake of C-RCM 650 is similar to that of C-RCM 400 and carbonated hydrated cement paste prepared at room temperature. However, the ratio of compressive strength to CO2 uptake of C-RCM 650 is far more than that of C-RCM 400 and carbonated hydrated cement paste, which shows a better overall performance. Highlights: Regenerated cementitious materials (RCM) are prepared from waste concrete. Carbonation reactivity of RCM is promoted by low temperature calcination. RCM possesses high net CO2 impact and excellent mechanical properties.